Going Viral : A Gravity Model of Infectious Diseases and Tourism Flows - Cevik, Serhan (IMF Working Papers; Working Paper, 2020)
This paper develops a gravity model framework to estimate the impact of infectious diseases on bilateral tourism flows among 38,184 pairs of countries over the period 1995-2017. The results confirm that international tourism is adversely affected by disease risk, and the magnitude of this negative effect is statistically and economically significant. In the case of SARS, for example, a 10 percent rise in confirmed cases leads to a reduction of as much as 9 percent in tourist arrivals. Furthermore, while infectious diseases appear to have a smaller and statistically insignificant negative effect on tourism flows to advanced economies, the magnitude and statistical significance of the impact of infectious diseases are much greater in developing countries, where such diseases tend to be more prevalent and health infrastructure lags behind.